Analisis Faktor-Faktor Penyebab Kesulitan Belajar Siswa Terhadap Mata Pelajaran Kompetensi Kejuruan Menggambar Teknik dengan Menggunakan Program Autocad - HN, Jeffrey Immanuel; Maulana, Arris (LPPM Universitas Negeri Jakarta, 2013)
The objective of this study to determine the factors that cause learning difficulties for vocational competence subjects Technical Drawing using AutoCAD program experienced by students of class XI Architecture Engineering Department of SMK Negeri 1 Jakarta Academic Year 2012/2013. Population are students of class XI Architecture Engineering for 50 students. Data collection instrument used in this study using a questionnaire with four alternative answers have then analyzed by the method of factor analysis using software Excel 2010. Analysis test conducted on instrument reliability and validity, in which the results of the test are 40 items of 43 items declared valid by the results of reliability r11 = 0,937.Results of this study showed that of the factors studied were internal factors including the physiological and psychological factors as well as external factors, including environmental factors both family environment, school and the community have an influence on the learning difficulties experienced by students. Percentage results obtained by each of the factors that explain the overall study of the factors that cause learning difficulties for students physiological factors gets low category with 4% mean value of 50 students who became the object of study only 2 students who have difficulty learning disorders caused by physiological conditions, whereas psychological factors are at sufficiently high category with a value of 41% means that there are 21 students who have difficulty learning disorders on psychological conditions and environmental factors have a value of 55%, comprising 25% of the family environment, school environment 16% and 14% of the communities, meaning there are 27 students who have learning disorders caused by environmental conditions